47th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2009
DOI: 10.2514/6.2009-1405
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Stable Boundary Layer Flows on Wind Turbine Fatigue Loads

Abstract: Near-neutral atmospheric stability conditions form the basis for wind turbine design. This is surprising since such near-neutral conditions occur in so-called transition periods only twice each day (around sunrise and sunset). Unstable conditions occur during the day and stable conditions occur generally at night. During nighttime stable conditions, turbulence is typically generated by shear and destroyed by negative buoyancy. Wind shear (both magnitude and direction) under stable conditions is much larger in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Future measurement campaigns can exploit collaborative measurements of dissipation rate using in situ measurements as used here and estimates from scanning lidar (e.g. Smalikho et al 2013;Aitken and Lundquist 2014c) to assess the variability of dissipation throughout turbine wakes and the validity of Taylor's frozen turbulence hypothesis for wake measurements. Dissipation likely reaches a maximum value at some distance downwind of the turbine and then decays further downwind.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Future measurement campaigns can exploit collaborative measurements of dissipation rate using in situ measurements as used here and estimates from scanning lidar (e.g. Smalikho et al 2013;Aitken and Lundquist 2014c) to assess the variability of dissipation throughout turbine wakes and the validity of Taylor's frozen turbulence hypothesis for wake measurements. Dissipation likely reaches a maximum value at some distance downwind of the turbine and then decays further downwind.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…Measurements of dissipation rate and the resulting erosion of a turbine wake or of a wind-farm wake are required to assess models of wake behaviour that are used for optimizing wind-farm layouts or quantifying annual energy production yields at wind farms under development. Smalikho et al (2013) showed a strong dependence of wake length with ambient background dissipation rate. Further, with the prospect of improved wake characterization on the horizon, theoretical efforts are now addressing the feasibility of optimizing wind-farm power production based on manipulating wakes (Marden et al 2012;Farm et al 2013).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…At present, the IEC guidelines explicitly address conditions associated only with the neutral boundary layer (NBL)-i.e., they ignore buoyancy effects in the definition of design load cases. In the present work and in ongoing studies [1][2][3][4], the authors are seeking to extend the design paradigm to allow a reliability-based assessment of wind turbines against fatigue and extreme limit states that includes evaluation of turbine loads for suites of inflow turbulence flow fields that have the spatial structure and characteristics that reflect a wide range of atmospheric stability conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wind shear, veer, and elevation-dependent turbulence variance particularly in the SBL (as distinct from the same in the NBL) have been recognized as having a significant influence on power generated as well as on loads experienced by utility-scale wind turbines with large rotor-swept areas [6][7][8]. Physics-based large-eddy simulation can be used to describe various realistic flow fields including those for the SBL [1,2,4,9]; on the other hand, stochastic simulation [10] is the accepted method of choice for the generation of IEC-NBL flow fields and its use, with spectral methods, is well documented in design standards and guidelines.…”
Section: Introductionmentioning
confidence: 99%